Cuidados de enfermería aplicado en paciente con cistocele grado III - Echeverria Banchon, Fatima Maria (2018)
The cystocele grade III, causes alterations in the quality of life of women having a negative impact at a social level, both aging and multiparity are the main risk factors for its development. In the following clinical case we present a female patient of 52 years of age with grade III cystocele, she had her controls in outpatient consultation due to the need to urinate frequently or urgently and pain in the epigastrium (heaviness), with antecedents Hypertension staff diagnosed 8 years ago is under treatment, is not allergic. As gynecobstetric background: getas 5, delivery 3, cesarean section 2, abortion none. As a treatment you need surgery to replace the bladder in place. The main objective of this case is the development of the nursing care process focused on the patient, achieving early recovery of the same. After following up, favorable results have been seen, especially with regard to their quality of life; so I come to the conclusion that you should treat people with this condition, not only for healing but to improve their quality of life.